A review of biomass thermal analysis, kinetics and product distribution for combustion modeling: from the micro to macro perspective - Silva, João Pedro Vasconcelos (2023)
Driven by its accessibility, extensive availability, and growing environmental consciousness, solid biomass has emerged as a viable alternative to enhance the diversity of renewable energy sources for electricity generation. To understand the phenomena involved in solid biomass conversion, it is necessary not only to understand the stages of the biomass combustion process but also to understand specifically the kinetics of the reaction and the release of the volatiles. The present work presents an overview of the existing literature on several topics related to the biomass combustion process, its characterization, as well as strategies to develop simple and effective models to describe biomass conversion with a view to the future development of numerical simulation models. Since the focus of most of the investigations is the development of a numerical model, a summary and identification of the different model assumptions and problems involved in thermal analysis experiments are presented. This literature review establishes the significance and credibility of the research, providing the main concepts and assumptions with a critique on their validity. Hence, this work provides specific contributions from a multi-scale perspective which can further be extended to provide insights into the design and optimization of biomass combustion technologies, such as boilers and furnaces.